Relevansi Hadis tentang Pencarian Jati Diri terhadap Krisis Identitas dan Hilang Arah pada Remaja Generasi Z di Era Media Sosial: Tinjauan Psikologi Perkembangan Eriksonian - Nasrulloh; Ema Ummiyatul Khusnah (LPPM IAI Hasanuddin Pare-Kediri, 2025)
The phenomenon of identity crisis and loss of direction among Generation Z adolescents has become increasingly concerning amid the dominance of social media. This study aims to analyze the relevance of the hadith on ma‘rifat al-nafs (“Whoever knows himself knows his Lord”) in relation to the psychological and spiritual problems faced by the digital generation from the perspective of Eriksonian developmental theory. The research employs a qualitative approach through a literature study of hadith scholarship, developmental psychology, and modern adolescent social phenomena. The findings reveal that Generation Z’s identity crisis arises from disconnection from spiritual values and the dominance of digital self-image. The hadith on ma‘rifat al-nafs offers a reflective paradigm that can restore spiritual and moral balance, while Erikson’s theory explains the psychosocial mechanisms of identity formation. The integration of these two perspectives produces a comprehensive approach to shaping adolescent identity that is both spiritually and socially grounded. This study emphasizes the importance of hadith-based Islamic education and counseling in addressing the existential disorientation of youth in the digital era.